Experimental investigations of tooth pitch variation and cutting parameters on areal surface texture in flat end milling of Fe–Ni alloy Supra50 - Ben Said, Mihed; Ftoutou, Ezzeddine; Hajjaji, Imed; Benkhalifa, Ated; Trigui, Moez (International journal of advanced manufacturing technology, 2025)
Surface texture is a key parameter in the machining of Fe–Ni alloys, which are widely used for their dimensional stability and low coefficient of thermal expansion, particularly in aeronautical applications subject to high mechanical and thermal stresses, such as aircraft solenoid valve parts. Among Fe–Ni alloys, SUPRA50 has proven its effectiveness and is currently a preferred choice for such applications. However, achieving a high surface quality remains a major industrial challenge when milling Fe–Ni alloys such as SUPRA50. This study experimentally analyses the effect of tool geometry—particularly tooth pitch variation and the number of teeth—as well as cutting parameters on areal surface texture parameters ( Sa , Sz , and Sq ) during milling operations using different flat end mill geometries. The results show that an increase in feed per tooth leads to a significant rise in Sa , Sz , and Sq values, thus deteriorating surface quality, particularly with constant pitch tools. In contrast, variable pitch tools exhibit significantly lower areal surface texture values, thereby improving surface quality due to their ability to disrupt regular excitation frequencies and stabilize the cutting process. Overall, these results highlight the beneficial role of tooth pitch variation and increased number of teeth in stabilizing the milling process and improving surface texture quality when machining Fe–Ni SUPRA50 alloy with flat end mills, in accordance with the analytical and numerical models reported in the literature.